ORAL CORRECTIVE FEEDBACK IN A SPEAKING CLASS - Imroatus Solikhah (Center of Language and Cultural Studies, 2016)
The objective of this study is to see kinds of corrective feedbacks used by English lecturer in speaking class. The study used classroom based observation as the design, assigning 30 students and one speaking lecturer in English department University of Bantara (UNIVET) Sukoharjo. Data were collected using observation and interview. The study revealed that teacher’s corrective feedback is one factor that influences the progress of students in learning English. It did not bother the students in building a communication. The evidence showed that that the teacher applied recasts, explicit correction, and clarification requests. Recasts was dominated the type of corrective feedback used by the teacher because it did not make the students confused. Three criteria of effective corrective feedback occurred in correction given by the teacher. He was consistent in treating the errors, gave correction without breaking the flow of the communication, and did not ridicule the students in giving correction.